Enhancing Information Technology Governance: A Comprehensive Evaluation Of The 2019 COBIT Framework In The Retail Industry - Viriyatama Lim, Marco; Indah Fianty, Melissa (International Journal of Science, Technology & Management, 2023)
A retail company faced challenges such as network issues, unreliable third-party databases, and a lack of employee understanding of input transactions and the introduction of new products or services. The research employed interviews and questionnaires to address these issues and assess the company's information technology governance using the 2019 COBIT framework. The findings would help identify appropriate processes to address the company's difficulties. The prioritized domains included APO12 - Risk Management, BAI03 - Solution Identification and Development, BAI06 - IT Change Management, and BAI10 - Configuration Management. The research revealed that APO12 reached level 3 (highly achieved), while BAI03 and BAI06 reached level 4 (significantly achieved), and BAI10 achieved level 4 (completely achieved), aligning with the company's expectations. These results determine the company's IT governance level and have the potential to enhance its capabilities.